Kinesiotaping Effects on Shoulder Pain, Mobilization and Functional Capacity in Leisure Basketball Athlete - Vitriana Biben (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Shoulder pain is a common issue among basketball players and it can decrease their range of motion (ROM) and overall upper limb functional ability. Kinesiotaping modulates pain mechanoreceptors on the skin and thus can reduce pain and impro ve shoulder ROM.Methods: This study aims to evaluate the effects of KT application on the severity of pain, shoulder mobilization, and functional ability of the upper limb in leisure basketball players. Quantitative quasiexperimental method with intervention design in 32 basketball leisure athletes was used. Pain was assessed by using the 100mm Numeric Rating Scale instrument, shoulder flexion and abduction were measured using a goniometer and the Shoulder Pain & Disability Index (SPADI) instrument was used to assess upper limb functional ability.Results: There was a significant decrease in shoulder pain (4.78±0.79 to 2.90±1.42 on day 5, p= 0.05), and an increase in flexion and abduction (on day 5, p=0.05 for flexion and p=0.05 for abduction). There was also a significant increase (p =0.05) in upper limb functional ability after the intervention.Conclusion: KT application shows benefits in decreasing shoulder pain and increasing shoulder mobilization and functional ability of upper limb during first 3rd day until 5th day application.Keywords: functional abilities, kinesiotaping, mobilization, pain, should er joint